Exploring the Therapeutic Potential of Glycyrrhizic Acid in Liver Implication in Dengue Infection: A Case Report - Putri, Indah Sagitaisna; Pipik Ripa'i; Donghwa Na; Herry Wibowo (Indonesian Journal of Tropical and Infectious Disease, 2024)
Dengue is one of the most common infectious diseases affecting humans. The virus is transmitted between humans by the Aedes mosquito. It occurs hyperendemically in tropical and subtropical climates worldwide. Dengue infection can affect numerous organs, with the liver being the most frequently affected organ. The clinical spectrum of liver disorders ranges from mild elevation of transaminase enzymes to severe conditions such as acute liver failure. Several mechanisms have been proposed to describe hepatic dysfunction observed in dengue fever and dengue hemorrhagic fever, such as immunological injury, hypoxic injury, and direct viral damage due to reduced hepatic perfusion during shock. Glycyrrhizic acid, extracted in the form of glycyrrhizin from the root of the licorice plant Glycyrrhiza glabra, is referred to as Stronger Neo-Minophagen-C (SNMC®). It has shown effectiveness in reducing serum aminotransferase and bilirubin levels, attenuating hepatocyte apoptosis, and producing endogenous interferon. The following is a case report of a 23-year-old woman with dengue fever and elevated liver enzyme level. The patient's vital signs were stable. A physical examination revealed no abnormalities. A complete blood count test showed thrombocytopenia without an elevation of the hematocrit. AST level was 901"‰U/L after admission. Causes of other hepatitis infections, such as hepatitis A, B, and C, were excluded. The dengue IgM and IgG antibody levels were reactive. After several days of hospitalization, the patient experienced clinical improvement after supportive therapy and the administration of glicyrrhizic acid or SNMC®.